Cultural and information space and divergence of modern societies - Radevich, Ekaterina V. (Journal of the Belarusian State University. Philosophy and Psychology, 2022)
The article is devoted to the study of modern trends in sociodynamics, which are appeared in the divergence of the world community in the context of globalisation. The decisive role is played by modern information and communication technologies (ICT), which form a synergistic unity with culture. To designate such unity, the work uses the concept of «cultural and information space», which demonstrates the integral interaction of culture and ICT, as a result of globalisation. It is through modern high technologies that globalisation affects culture and demonstrates a new trend in its development – the divergence of modern society, which manifests itself in various unstable and unsteady conditions of the world whole such as national and religious-ethnic confrontations, military conflicts (on the example of J. Friedman’s work), as well as hybrid conflicts that are becoming an integral attribute of modern society. Special attention is paid to information and cyber wars, as a manifestation of hybrid conflicts, which are a natural result of the development of ICT in the context of globalisation.